2019
DOI: 10.1021/acs.jpcc.9b00981
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two Problems of Specific Reaction Parameter Density Functional Theory: Sticking and Diffraction of H2 on Pt(111)

Abstract: It is important that theory is able to accurately describe dissociative chemisorption reactions on metal surfaces, as such reactions are often rate-controlling in heterogeneously catalyzed processes. Chemically accurate theoretical descriptions have recently been obtained on the basis of the specific reaction parameter (SRP) approach to density functional (DF) theory (DFT), allowing reaction barriers to be obtained with chemical accuracy. However, being semiempirical, this approach suffers from two basic probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…The molecular beam experiments of Cao et al 60 are not as well described by the B86SRP68-DF2 DF, as can be seen in figure S7. However we note that the increase of the MAD value in going from figure 8a to figure S7a is similar in size to what was reported for the PBEα57-DF2 DF 65 (see table S9). Earlier work from our group has shown that the experimental results of Luntz et al 64 and Cao et al 63 are in good agreement with each other for the lower incidence energies but somewhat diverge for the higher incidence energies 65 .…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 86%
See 4 more Smart Citations
“…The molecular beam experiments of Cao et al 60 are not as well described by the B86SRP68-DF2 DF, as can be seen in figure S7. However we note that the increase of the MAD value in going from figure 8a to figure S7a is similar in size to what was reported for the PBEα57-DF2 DF 65 (see table S9). Earlier work from our group has shown that the experimental results of Luntz et al 64 and Cao et al 63 are in good agreement with each other for the lower incidence energies but somewhat diverge for the higher incidence energies 65 .…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 86%
“…The reason for taking this approach, instead of fitting the DF to best reproduce experiments on all systems shown in the results section, is that numerous experimental results are available for the reaction of H 2 and D 2 on Cu(111) [45][46][47][48][49][50][51][52][53][54][55] . For the non-copper systems discussed in this work experimental results are sparse 17,70 , and there is discussion about the validity of the available parameters describing the molecular beams used in the experiments on H 2 (D 2 ) + Ag (111) and Pt(111) 19,60,64,65 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations